Enhanced physical properties of TiSi2 doped Gd2Zr2O7 ceramic for thermal barrier coatings. (22nd February 2019) - Hua, Yinqun; Jiang, Bochen; Chen, Ruifang; Cao, Jiangdong; Shuai, Wenwen; Li, Ruitao
Abstract: In this study, Gd2 Zr2 O7 -X TiSi2 (X = 0, 2.5, 5 and 7.5 wt% TiSi2 ) ceramics were synthesized by solid state reaction method at 1550 °C for 12 h in air. The influences of TiSi2 content on the phase, microstructure, thermophysical properties, hardness and fracture toughness were investigated. Gd2 Zr2 O7 - X TiSi2 (X = 7.5 wt%) ceramic mainly consists of a defect fluorite phase; while Gd2 Zr2 O7 -X TiSi2 (X = 0, 2.5 and 5 wt% TiSi2 ) ceramics have an ordered pyrochlore phase. In addition, the degree of structural order decreased with the increasing TiSi2 content. The microstructure of the doped ceramic materials exhibited grain refinement. The doping of TiSi2 decreased the thermal conductivity while improved the thermal expansion coefficient, the hardness and the fracture toughness enhanced significantly. With these improved properties, the TiSi2 doped Gd2 Zr2 O7 ceramic materials can be a very promising material for ceramic layers of thermal barrier coating.